2006
DOI: 10.4049/jimmunol.177.6.3806
|View full text |Cite
|
Sign up to set email alerts
|

Immature Dendritic Cells Suppress Collagen-Induced Arthritis by In Vivo Expansion of CD49b+ Regulatory T Cells

Abstract: Dendritic cells (DCs) are specialized APCs with an important role in the initiation and regulation of immune responses. Immature DCs (iDCs) reportedly mediate tolerance in the absence of maturation/inflammatory stimuli, presumably by the induction of regulatory T cells. In this study, we show for the first time that repetitive iDC injections trigger the expansion of a novel regulatory population with high immunomodulatory properties, able to protect mice from collagen-induced arthritis. These regulatory T cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
99
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(107 citation statements)
references
References 27 publications
6
99
2
Order By: Relevance
“…Because vaccination with 1 ϫ 10 6 tolerogenic DCs was not sufficient to cure disease, we increased the dose of tolerogenic DCs to 2.5 ϫ 10 6 per vaccination, a dose that is sufficient to prevent CIA using TNF-treated tolerogenic DCs (18)(19)(20). However, there is a risk involved in increasing the dose of tolerogenic DCs: another study showed that a dose of 2.5 ϫ 10 6 TNF-treated DCs was pathogenic (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because vaccination with 1 ϫ 10 6 tolerogenic DCs was not sufficient to cure disease, we increased the dose of tolerogenic DCs to 2.5 ϫ 10 6 per vaccination, a dose that is sufficient to prevent CIA using TNF-treated tolerogenic DCs (18)(19)(20). However, there is a risk involved in increasing the dose of tolerogenic DCs: another study showed that a dose of 2.5 ϫ 10 6 TNF-treated DCs was pathogenic (22).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, DCs transduced with FasL or IL-4 have been used to prevent CIA and to inhibit arthritis symptoms in mice with established disease (15)(16)(17). Tolerogenic DCs modified by drugs (dexamethasone; Bay 11-7082) or cytokines (tumor necrosis factor [TNF]) have been used successfully to prevent the onset of CIA (18)(19)(20)(21)(22) or to suppress established arthritis in a different model, the antigeninduced arthritis model (23).…”
Section: Conclusion Treatment With Type II Collagenpulsed Tolerogenimentioning
confidence: 99%
“…Starting at day 21, paw thickness was measured 3 times a week with a Mitutoyo micrometer (Sigma-Aldrich), and the severity of arthritis was graded by macroscopic examination as previously described. 23 After euthanasia, the knee joints were collected and incubated for 24 hours in RPMI 1640 (300 L). Supernatants were stored until quantification of cytokines by enzyme-linked immunosorbent assay (ELISA).…”
Section: Cia Model and Clinical Evaluationmentioning
confidence: 99%
“…The mechanisms are, however, different in that IL-10 DC skew the response toward Th2 polarization, while DX-DC inhibit Th1 development by inducing IL-10-producing T cells [59]. Also collagen II-loaded, non-manipulated immature DC can inhibit CIA via the expansion of Treg [60]. One important issue to be considered is the number of injected DC: TNF-a-DC have been shown to be effective in inhibiting CIA and in inducing Treg only when injected at low doses (10 5 cells) [61].…”
Section: Drive Cd4mentioning
confidence: 99%